Flow characterization and structural alterations in Ahmed glaucoma FP7 tubes after in-vitro aging in silicone oil. - Abu Tahir Taha; Matthew Clarke; Chiara Wabl; Ying Han; Frank Brodie (PLoS ONE)
Purpose Patients with intraocular silicone oil (SO) display higher odds of surgical failure after Ahmed glaucoma valve (AGV) implantation compared to patients without SO. However, the structural impact of SO exposure on silicone-made AGV tubes and the resulting changes in flow rate remain unexplored. This in-vitro study evaluated changes in tube dimensions and flow rates of AGV FP7 tubes after SO exposure to inform clinicians how such changes may impact AGV functionality. Methods AGV FP7 tube segments underwent accelerated aging to approximate 90 days of exposure to the following media: Balanced Salt Solution (BSS), 1000 centistokes (cs) SO, and 5000cs SO. Tube dimensions were measured before and after aging. A constant gravity flow test setup was created to measure flow rates through tubes before and after aging. The students' T-test was used to compare the mean change between groups post-aging. Results Post-exposure, 1000cs and 5000cs SO tube segments increased in length by 5.94% and 5.55%, respectively, compared to 0.38% of BSS tubes (P < 0.05 for both). The inner lumen area expanded for tube segments in 1000cs and 5000cs SO by 11.75% and 2.70%, respectively, but contracted for tubes in BSS by -2.70% (P < 0.01 and P = 0.068 for 1000cs and 5000cs SO, respectively). Post aging, the flow rates increased on average by 61.0% and 98.6% for 1000cs and 5000cs SO, respectively, whereas flow rates for BSS tube segments slightly decreased by -4.92%. The difference was statistically significant for BSS vs. SO groups (P < 0.01 for both). Conclusions Prolonged exposure to SO structurally altered the AGV FP7 tube segments by expanding their cross-sectional area, potentially leading to increased flow rates. These results may inform clinicians about potential in-vivo interactions in patients with the simultaneous presence of glaucoma drainage devices and intraocular SO.